KARAKTERISTIK PROKSIMAT DAN SENSORI STIK TULANG IKAN TONGKOL (Euthynnus affinis) DAN IKAN KAKAP MERAH (Lutjanus sp.) - Nara, Selfia Martha; Bugis, Iskandar; Kabrahanubun, Ignasia; Tuarita, Mirna Zena (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2022)
Fishbone sticks are one of the fisheries waste products by utilizing mackarel tuna fish fishbone (Euthynnus affinis) and red snapper fishbone (Lutjanus sp.). The aim of this study was determine the proximate content and level of acceptance of stick product through sensory analysis. This study used a desciptive exploratory method. Result showed that the highest value of water, fat and protein compund in mackarel tuna fish fishbone stick was 3.58%, 34,97%, and 9.45% respectively. The organoleptic test result which differ in terms of appearance, aroma, taste, and texture are the red snapper fishbone preferred with the average value 7.98.